Detection of antibodies against Mycoplasma gallisepticum and Mycoplasma synoviae in day-old broiler chicks and broilers - GEORGIADES (Γ.Κ. ΓΕΩΡΓΙΑΔΗΣ), G. K. (Journal of the Hellenic Veterinary Medical Society, 2018)
During the last decade, in die Clinic of Poultry Diseases, 882 sera were examined for the detection of antibodies against Mycoplasma gallisepticum (M.g.) and Mycoplasma synoviae (M.s.), which are usually involved in the respiratory diseases of broilers. Out of these sera, 188 derived from day-old broiler chicks and 694 from broilers with respiratory disease. Rapid serum agglutination test was used as diagnostic method. Among day-old broiler chick sera, 40 (21.27%) were M.g. positive, while 76 (40.42%) were M.s. positive. Among broiler sera, 133 (19.16%) were M.g. positive, while 356 (51.29%) were M.s. positive. The results of the present study show that the prevalence of the M.s. positive sera is significantly higher (P<0.001) than this of the M.g. positive sera, not only in day-old broiler chicks, but also in broilers, which indicates the greater importance of M.s. in the occurrence of respiratory disease in these birds.